Accesibilidad urbana a la atención médica primaria: estudio comparativo de Canadá, EE.UU. y de Chile - Scarpaci, Joseph L. (Investigaciones Geográficas: Una mirada desde el sur, 1984)
The question of accessibility to primary medical care is examined for three medical systems; the large private market in the United States and the predominantly state-financed systems in Canada and Chile. Major health policies in these countries are reviewed and the spatial patterns of primary care physicians and centers are described. Comparative findings reveal that private physicians’ preference for locating in pleasant residential settings in both Canada and Santiago, Chile is an indication that the more state-financed medical systems tend to be weaker agents of disperion than the free-market structure of the U.S. Unlike Canada and Chile, the locational attributes of primary care practitioners in the U.S. are their proximity to suburban retail districts and major thoroughfares of automobile travel.